Peran Digital Green Marketing dalam Meningkatkan Green Purchase Intention Generasi Z - Saputra, Alya Widi; Agustin, Raina Agnibrata; Chaerani, Safira Salsabila; Salsabila, Saskia (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
Digital transformation and increasing environmental awareness are driving companies to adopt digital-based green marketing strategies. This study aims to analyze the role of digital green marketing in increasing green purchase intention among Generation Z. Generation Z is a group of digital native consumers who have high sensitivity to sustainability issues. This study uses a quantitative approach with a survey method on Generation Z who actively use digital media. The sampling technique was purposive sampling. Data analysis used linear regression to test the effect of digital green marketing on green purchase intention. The results show that digital green marketing has a positive and significant effect on green purchase intention of Generation Z. Digital marketing strategies that emphasize environmental education, information transparency, and sustainability values ​​​​have proven effective in increasing interest in purchasing environmentally friendly products.